2018
DOI: 10.1002/mabi.201800419
|View full text |Cite
|
Sign up to set email alerts
|

Tubule Nanoclay‐Organic Heterostructures for Biomedical Applications

Abstract: Natural halloysite nanotubes (HNTs) show unique hollow structure, high aspect ratio and adsorption ability, good biocompatibility, and low toxicity, which allow for various biomedical applications in the diagnosis and treatment of diseases. Here, advances in self‐assembly of halloysite for cell capturing and bacterial proliferation, coating on biological surfaces and related drug delivery, bone regeneration, bioscaffolds, and cell labeling are summarized. The in vivo toxicity of these clay nanotubes is discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 63 publications
(93 reference statements)
1
59
0
Order By: Relevance
“…[ 19 ] Gaharwar et al [ 20 ] reviewed the potential of laponite nanoclay and its nanocomposites for additive manufacturing and regenerative medicine. Liu et al [ 21 ] reported an overview of halloysite nanotubes and respective nanocomposites for various biomedical applications such as drug delivery, biosensing, and bone regeneration. Chimene et al [ 22 ] extensively reviewed nanoclay reinforced hydrogels as bioinks for 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Gaharwar et al [ 20 ] reviewed the potential of laponite nanoclay and its nanocomposites for additive manufacturing and regenerative medicine. Liu et al [ 21 ] reported an overview of halloysite nanotubes and respective nanocomposites for various biomedical applications such as drug delivery, biosensing, and bone regeneration. Chimene et al [ 22 ] extensively reviewed nanoclay reinforced hydrogels as bioinks for 3D bioprinting.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Biohybrid materials with variable structures and morphologies were successfully prepared by the assembly of natural polymers and inorganic particles. [12][13][14] Nowadays, these systems are attracting the attention of material scientists and engineers due to their wide applications including biomedical technology, catalysis, remediation, cultural heritage treatment and food packaging. [15][16][17][18][19][20][21][22][23][24] Recently, great efforts have been addressed to the design of biohybrid materials composed of organic moieties and inorganic clay minerals, which can present different features in terms of chemistry, aspect ratio, morphology and charge.…”
Section: Introductionmentioning
confidence: 99%
“…[65] Ester derivative of hyaluronic acid was used in the evaluation of the adipogenic potential for sponges with varying pore sizes and Morphology and crystal structure of HNTs: A) scanning electron, B) atomic force microscopy images, [31] and C) crystal structure. [32] Adapted with permission. [31] Copyright 2015, Springer Nature Publishing AG, [32] Copyright 2019, John Wiley & Sons, Inc.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…[32] Adapted with permission. [31] Copyright 2015, Springer Nature Publishing AG, [32] Copyright 2019, John Wiley & Sons, Inc.…”
Section: Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation